Milenials consumer behavior and it’s influence on purchase decisions of halal cosmetic products - Yudha, Ana Toni Roby Candra; Haryono, Slamet (Universitas Negeri Surabaya, 2024)
The stretching development of the global halal industry, including Indonesia, continues to receive consumers' attention. Among the many sectors that attract consumers' interest is cosmetics, especially with a halal label; product quality supported by promotions by public figures continues to encourage consumers' desire to use halal cosmetics. This study aims to confirm the influence of millennial consumer behavior on purchasing decisions for halal cosmetic products. A random confirmation process of the respondents accompanies this quantitative research method. There were 120 respondents who were dominated by women millennials, with the SmartPLS test tool and a Likert scale of degree 4. The research results were among the four independent variables. Halal labels and sales services had no effect, while product quality and consumer ratings affected purchasing decisions for halal cosmetics. At the confirmation level, it is known that halal labels and sales services get respondents' attention; even without knowledge about them, they immediately buy products because of brands, influencers, and friend recommendations. So, the halal label and sales service does not have a significant effect; instead, it is an attitude of 'ignorance' and is more due to brand or influencer education, as previously stated.